PENGARUH PEMBELAJARAN IPA BERBASIS PHET TERHADAP MOTIVASI DAN HOTS SISWA SMP - Mega Puspita Sari, Mega; Indrawati, Indrawati; Budiarso, Aris Singgih (EduFisika: Jurnal Pendidikan Fisika, 2021)
The research aims to examine the effect of PhET based science learning on junior high school students' motivation and Higher Order Thinking Skills (HOTS). This type of research is a quasi experimental design with a non-equivalent control group design. The research sample was students of class VII B as the experimental class as many as 30 students and class VII C as the control class as many as 30 students carried out at MTs Negeri 4 Banyuwangi. Data collection was done by using test techniques, questionnaires, interviews and documentation. The data analysis technique used the independent sample t-test. The results showed that science learning based on PhET had a significant effect on student motivation and had no significant effect on Higher Order Thinking Skills (HOTS) of junior high school students.